1994
DOI: 10.1007/bf00176436
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical light and electron microscopy of basal laminar deposit

Abstract: The formation of basal laminar deposit (BLD) is one of the histopathologic changes in the aging human macula. BLD is assumed to be an early stage of age-related macular degeneration. The location of BLD, between the RPE plasma membrane and its basement membrane and in the outer collagenous zone of Bruch's membrane, and its ultrastructure suggest that it is composed of excessive amounts of basement membrane material. The main components of basement membranes are type IV collagen, heparan sulfate proteoglycans (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 18 publications
6
39
1
1
Order By: Relevance
“…The location and composition of these deposits distinguish aging from AMD. Basal laminar deposits (BlamD), which form between the RPE cell and basement membrane, are a normal aging change early, but become specific for AMD when they become thick and contain cellular debris, 'long spaced collagen', membranous structures, lipid, and inflammatory proteins (Sarks, 1976;Newsome et al, 1987;Green and Enger, 1993;van der Schaft et al, 1994;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999;Anderson and Ozaki, 2001;Johnson et al, 2002;Leu et al, 2002). The most sensitive and specific histopathologic marker of AMD is basal linear deposits (BlinD), which form in the inner collagenous layer of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location and composition of these deposits distinguish aging from AMD. Basal laminar deposits (BlamD), which form between the RPE cell and basement membrane, are a normal aging change early, but become specific for AMD when they become thick and contain cellular debris, 'long spaced collagen', membranous structures, lipid, and inflammatory proteins (Sarks, 1976;Newsome et al, 1987;Green and Enger, 1993;van der Schaft et al, 1994;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999;Anderson and Ozaki, 2001;Johnson et al, 2002;Leu et al, 2002). The most sensitive and specific histopathologic marker of AMD is basal linear deposits (BlinD), which form in the inner collagenous layer of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The composition and location of these deposits distinguishes chronological aging from age-related disease. Basal laminar deposits, which develop between the RPE cell and basement membrane, are specific for age-related macular degeneration (AMD) when they are thick and contain heterogeneous debris such as long spaced collagen (Sarks, 1976;Newsome et al, 1987;Green and Enger, 1993;van der Schaft et al, 1994;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999;Anderson et al, 2001;Johnson et al, 2002;Leu et al, 2002). Basal linear deposits occur within the inner collagenous layer, and are the most specific basal deposit for AMD (Sarks, 1976;Newsome et al, 1987;Green and Enger, 1993;van der Schaft et al, 1994;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999;Anderson et al, 2001;Johnson et al, 2002;Leu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Early deposit formation is the result of normal basement membrane component expansion (38)(39)(40). Further evidence of overlap between D-gal-induced transcriptional changes in the RPEchoroid and atherosclerosis is the altered expression of matrix genes.…”
Section: Discussionmentioning
confidence: 99%
“…These include Sorsby's fundus dystrophy, late onset retinal degeneration (LORD), adult foveomacular pigment epithelial dystrophy and Malattia leventinese (115). The molecular composition and origin of BLamD have not yet been identified (116)(117)(118), but their morphological similarity to long-spacing collagen is striking. Electron microscopy has revealed that their banding pattern matches that of type VI collagen (119).…”
Section: Morphological Correlates Of Early Amdmentioning
confidence: 99%